Penerapan Model Contextual Teaching and Learning Untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik kelas IV SD Negeri 02 Kabawetan - tri hardianti; nani yuliantini; herman lusa (Universitas Bengkulu, 2021)
Abstract The objectives of this research were to describe steps of Contextual Teaching and Learning model to increase teachers' and students' activities in thematic teaching, and to increase students' grade in thematic teaching of the fourth grade of SD Negeri 02 Kabawetan by applying Contextual Teaching and Learning (CTL) model. This was a class action research. The subjects were teachers and students of the fourth grade of SDN 02 Kabawetan. The research instruments were observation sheet and test sheet. The observation data were analyzed using average score formula, highest score, lowest score, score ratio and score range for each criterion. The test data were analyzed using score average formula and percentage of classical completeness. The results showed there was increase of activities and students' grade in thematic teaching using CTL model. These were proven by the score of the first cycle of teachers' activity which was 28, and increased in the second cycle which was 30,3. Students' score for first cycle was 9.5 with category of fair and increased in the second cycle with a score of 12.6 with category of good. The grade for first cycle of Indonesian Language class showed the average score was 66.2 with classical completeness of 52.94%, there was an increase of grade in the second cycle in which the average score was 78.9 and the classical completeness was 82.35%. For the Science class, in first cycle the average score was 69.18 and classical completeness was 58.8%; there was an increase in the second cycle, the average score was 84.28 and classical completeness was 100%. Thus, the application of Contextual Teaching and Learning model could increase activities and students' grade in thematic teaching of the fourth grade of SDN 02 Kabawetan. Keywords : Contextual Teaching and Learning model, learning activities, students' grade